Is the parti-coloured bat Vespertilio murinus Linnaeus, 1758 a common bat species in Slovenia? - Primož Presetnik; Monika Podgorelec; Alenka Petrinjak (Natura Sloveniae)
In the last overview of bats in Slovenia, the parti-coloured bat Vespertilio murinus was one of the rarest species listed. However, in the past few years (June 2005 - April 2013) we have found 98 new locations. In this article, we present new data on mating sites, summer roosts and hibernacula, as well as other chance encounters. Although V. murinus is a permanent part of the bat fauna in Slovenia, it is much more evident during the colder part of the year, when migrating individuals possibly reach their wintering area. We argue that this bat species is much more common in Slovenia and its neighbouring regions than previously assumed.